Nilai-Nilai Sejarah Toponim Wilayah Kabupaten Lahat Sebagai Sumber Pembelajaran Sejarah Di Sma Negeri 2 Lahat - Putri, Atika Rahmania; Kristiawan, Muhammad; Suryani, Suryani (JPT : Jurnal Pendidikan Tematik, 2021)
Toponym is a discussion about the origin of the naming of places, regions and a part of the earth's surface, including natural ones (rivers, oceans, and mountains) that are artificial (cities, buildings, roads, bridges) toponymy is related to the fields of technology and culture, which are related to history. , myth, or legend of a place. Which is in Lahat Regency, precisely in the District of Kota Lahat Pada, which aims to determine the historical values contained therein. To find out the source of history learning at SMA Negeri 2 Lahat this research method is descriptive qualitative, and data collection techniques use field data such as documentation, observation, interview. Data analysis techniques with data reduction, data presentation, and drawing conclusions. With the results of the study, it can be concluded that the historical values of the regional toponyms contained that are useful and useful for students to increase knowledge as a learning resource.